ADolescent and prEconception health peRspectiVe of Adult Non-communicable diseases (DERVAN): protocol for rural prospective adolescent girls cohort study in Ratnagiri district of Konkan region of India (DERVAN-1). Issue 9 (6th September 2020) - Patil, Suvarna; Patil, Netaji; Joglekar, Charudatta; Yadav, Arvind; Nilawar, Anup; Banavali, Ulka; Bhat, Rohit; Dombale, Vijay; Warpe, Bhushan; Mohite, Rachana; Joshi, Kiran
Abstract : Introduction: Precise impact of nutritional insufficiencies in adolescence as a risk factor for non-communicable diseases (NCD) in later life as adults remains largely unknown. We are conducting research into the effects of nutrition on adolescent girls of Ratnagiri district by a prospective cohort study (aDolescent and prEconception health peRspectiVe of Adult Non-communicable diseases cohort). Our study focuses on the physical health, nutritional parameters and cognitive profiles of adolescent girls, during the prenatal and postnatal period and we aim to follow this cohort and their offspring for 20 years. Methods and analysis: Cohort recruitment began in June 2019. Our aim is to recruit more than 1500 adolescent girls, age 16–18 years, over a period of 3 years. The recruit's cognition, diet and physical activity will be recorded. The following investigations will be performed: body composition by anthropometry and bioimpedence, and blood pressure, fasting blood sample to measure glucose, insulin, lipids, micronutrients and hormones, abdominal ultrasonography to measure liver, pancreas and kidneys. A biorepository has been created for long-term storage of blood, urine and saliva samples for future analysis. By this longitudinal study, we aim to identify the effects of malnutrition on the behavioural and biological measures in adolescent subjects and evaluate if these are associated with the onset of NCDs in adulthood. Ethics and dissemination: Institutional Ethic Committee (IEC) of BKL Walawalkar Rural Medical College and Hospital has granted the permission to carry out the study. IEC is registered with Government of India. Its registration code is EC/755/INST/MH/2015/RR-18. It is not a clinical trial but as required we have also registered the study on Clinical Trial Registry of India (CTRI). The registration code is CTRI/2019/04/018453. Appropriate written informed consent and assent are obtained from the parents and the adolescent girls, respectively. We plan to publish our results in peer-reviewed journals.